Kepemimpinan; Pengembangan Organisasi, Team Building dan Perilaku Inovatif (Studi Kepemimpinan Kepala Sekolah MA Hasyim Asy'ari Jogoroto Jombang) - Illa Zahroh Luthfita (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
The school principal was instrumental in increasing the motivation of teachers work. It can not be separated from the responsibility of principals as leaders of educational institutions. The success is the success of the school principal. The main key principals as effective leaders are able to influence and mobilize teachers to participate in school activities in order to realize the vision and mission of the school. The role of the principal in increased motivation of teachers working in MA. Hasyim Asy'ari with techniques namely: as partners, participators, supporters, provide the credentials, make the workplace a pleasant and uswah (example) for teachers MA. Hasyim Asy'ari. The role played by principals above and then move teachers to have the motivation to work is quite high.